Two alternative models concerning the perialveolar microcirculation in mammalian lungs - GÜNTHER,BRUNO (Sociedad de Biología de Chile, 2005)
Despite the fact that the concept of sheet-flow in the pulmonary microcirculation of mammals was introduced more than three decades ago, the capillary circulatory model still prevails in the physiological literature. Since cardiac output is identical in the systemic and in pulmonary circulations, it is noteworthy that in the former, the resulting arterial pressure is five times higher than that of the latter, which means that the corresponding microcirculations must be radically different. The present study addresses this problem from both morphological and physiological perspectives.